Tinjauan Sosio Ekonomi Gudeg Dan Preferensi Konsumennya Di Kotamadya Yogyakarta - Henry Yuliando, Stephanus Sri Hedy Agung Putra, Wahyu Supartono, (Widya Mandala Surabaya Catholic University, 2001)
Gudeg is the most popular javanese food in Yogyakarta, which is divided into two types; wet and dry. The difference of them depended on their moisture content. Its moisture content caused differences on the product attributes. Aims of this research were identifying the socio-economic aspects of gudeg producers and measuring consumer preferences level. The research on the gudeg producer was conducted and analysed by using Bivariate Correlation and Joint Correlation (Partial Correlation) procedures. Based on the results, it could be stated, that the difference types of gudeg influenced by profit, price and marketing area. Consumers research was conducted by using attitude index analysis. The results were, that dry gudeg lead attitude index by 0.655 and wet gudeg by 0.104. It meant that the consumers more prefered to consume dry gudeg than wet gudeg.